2018
DOI: 10.1161/jaha.118.008744
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Prediction in Acute Stroke Patients by Continuous Glucose Monitoring

Abstract: BackgroundThe purpose of this study was to examine the relationships between glucose parameters obtained by continuous glucose monitoring and clinical outcomes in acute stroke patients.Methods and ResultsConsecutive patients with acute ischemic stroke or intracerebral hemorrhage within 24 hours after onset were included. A continuous glucose monitoring device (iPro2) was attached for the initial 72 hours after emergent admission. Eight glucose parameters were obtained from continuous glucose monitoring: maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 44 publications
(66 reference statements)
1
48
0
Order By: Relevance
“…Blood markers are promising to aid in the risk stratification and individual treatment of ischemic stroke (21,22). A line of evidence have shown that elevated blood glucose levels are associated with unfavorable outcome in the patients with ischemic stroke (3, [23][24][25][26]. However, since hyperglycemia at the acute phage of ischemic stroke could be due to poor control of glucose in the diabetic patients, most prior studies excluded the diabetic patients (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Blood markers are promising to aid in the risk stratification and individual treatment of ischemic stroke (21,22). A line of evidence have shown that elevated blood glucose levels are associated with unfavorable outcome in the patients with ischemic stroke (3, [23][24][25][26]. However, since hyperglycemia at the acute phage of ischemic stroke could be due to poor control of glucose in the diabetic patients, most prior studies excluded the diabetic patients (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Increased blood glucose level is also associated with progression of infarction, reduced recanalization and poor clinical outcome [ 143 ]. Continuous glucose monitoring systems have been deployed to reduce stroke-related risks in both diabetic and non-diabetic stroke patients [ 144 ].…”
Section: Prevention and Treatment Strategies For Strokementioning
confidence: 99%
“…To our knowledge, few studies have used continuous glucose monitors in acute IS [ 7 , 8 , 26 28 ]. A relationship has been found between GV (by means of the standard deviation of mean glucose levels) and infarct growth [ 8 ], as well as between GV and early neurological deterioration [ 29 ].…”
Section: Discussionmentioning
confidence: 99%